Perlindungan Hukum Indikasi Geografis dalam UU No. 20 Tahun 2016 : Analisis Mekanisme Pendaftaran Kain Tenun Bima - Feni Aryani; Beverly Evangelista; Hanifah Mutiah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the legal protection of Geographical Indications (GI) for Kain Tenun Bima under Law No. 20 of 2016 concerning Trademarks and Geographical Indications, with a focus on the registration mechanism. Kain Tenun Bima, or Tenun Mbojo, is a cultural heritage of the Bima community, possessing high cultural and economic value. However, as of June 2024, this fabric has not yet been registered as a GI, leaving it vulnerable to counterfeiting and misuse by unauthorized parties. The research employs a normative method with a descriptive-analytical approach, examining primary data such as UU No. 20 Tahun 2016 and secondary data from journals, books, and government documents. The findings reveal that Kain Tenun Bima meets all GI criteria, including geographical origin, natural and human factors, and unique characteristics. GI registration offers legal, economic, and cultural benefits, such as protection against counterfeiting, increased market value, and preservation of cultural heritage. The GI registration process involves administrative and substantive stages by the Direktorat Jenderal Kekayaan Intelektual (DJKI),, requiring comprehensive documentation of the product's uniqueness. Challenges in registration include a lack of legal understanding and coordination among stakeholders. Therefore, collaboration between the government, weaving communities, and academics is essential to accelerate the GI registration for Kain Tenun Bima, ensuring legal protection and sustainability as a regional cultural and economic asset.